1967
DOI: 10.1002/pol.1967.150050601
|View full text |Cite
|
Sign up to set email alerts
|

Studies on poly(vinyl chloride). III. The role of the precipitated polymer in the kinetics of polymerization of vinyl chloride

Abstract: In polymerization of vinyl chloride monomer, free radicals precipitate on or within aggregatm of partidy swollen dead polymer. Polymerization on the solid polymer is characterized by autoaccelerating rates due to a progressive reduction in termination rate.This reduction in termination rate is due to the fact that as the reaction progresses and more polymer accumulates there is a decrease in probability that chain transfer of polymer radicals to monomer will generate a mobile radical, which can readily termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Equation 9 indicates that the monomer phase is practically pure. In agreement with original state ments by Cotman, et aL (12), polymer chains having about 25 monomer units become insoluble and disappear from the liquid phase by coalescence with larger particles. A similar qualitative description of phase, partition has been described in Ref.…”
Section: Model Developmentsupporting
confidence: 89%
“…Equation 9 indicates that the monomer phase is practically pure. In agreement with original state ments by Cotman, et aL (12), polymer chains having about 25 monomer units become insoluble and disappear from the liquid phase by coalescence with larger particles. A similar qualitative description of phase, partition has been described in Ref.…”
Section: Model Developmentsupporting
confidence: 89%
“…( size range. This hypothesis is supported by the data of Cotman et al 5 which show a very large number of these small particles at extremely low conversions (<l%); yet for conversion above 1%, there is a sharp decrease in the number of particles and the mean particle size has increased to 0.5-1 p. Further evidence in support of this mechanism comes from the papers and patent of T h~m a s *~-~l which indicate that a conversion of -7% is required before the polymer particles are structurally stable.…”
Section: Development Of the Polymer Particle Structuresupporting
confidence: 81%
“…Many papers in literature deal with the bulk polymerization of vinyl chloride (VC) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In all of them it is reported that the reaction has an accelerated behaviour and that the formed polymer separates as particles swollen by monomer from the onset of the process.…”
Section: Introductionmentioning
confidence: 99%